2001
DOI: 10.1103/physrevlett.86.2874
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Dissipation and Fluctuations in Individual Nanomagnets Measured by Ultrasensitive Cantilever Magnetometry

Abstract: Cantilever magnetometry with moment resolution better than 10(4)micro(B) was used to study individual nanomagnets. By using the fluctuation-dissipation theorem to interpret measurements of field-induced cantilever damping, the low frequency spectral density of magnetic fluctuations could be determined with resolution better than 1micro(B) Hz-1/2. Cobalt nanowires exhibited significant magnetic dissipation and the associated magnetic fluctuations were found to have 1/f frequency dependence. In individual submic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
175
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(184 citation statements)
references
References 24 publications
5
175
4
Order By: Relevance
“…Recently, however, it has been reported that the application of a magnetic field can cause significant mechanical dissipation in micromechanical oscillators made of nominally nonmagnetic Si. 7,[9][10][11] As shown in Fig. 1, this kind of dissipation has also been observed as a loss in mechanical quality factor Q in some bare ultrasensitive Si cantilevers used for recent MRFM.…”
Section: A Geometry For Optimizing Nanoscale Magnetic Resonance Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, it has been reported that the application of a magnetic field can cause significant mechanical dissipation in micromechanical oscillators made of nominally nonmagnetic Si. 7,[9][10][11] As shown in Fig. 1, this kind of dissipation has also been observed as a loss in mechanical quality factor Q in some bare ultrasensitive Si cantilevers used for recent MRFM.…”
Section: A Geometry For Optimizing Nanoscale Magnetic Resonance Forcementioning
confidence: 99%
“…For mechanical oscillators containing magnetic materials, dissipation that depends on magnetic field is expected and has been observed. 7,8 Magnetic dissipation should not affect oscillators containing no magnetic material. Recently, however, it has been reported that the application of a magnetic field can cause significant mechanical dissipation in micromechanical oscillators made of nominally nonmagnetic Si.…”
Section: A Geometry For Optimizing Nanoscale Magnetic Resonance Forcementioning
confidence: 99%
“…Stipe et al used cantilever magnetometry to show that the audio frequency thermomagnetic fluctuations were indeed much less in Pr 2 Fe 14 B than in cobalt. 134 These studies motivated a switch from nickel and cobalt to rare-earth magnets such as Sm 2 Co 17 and Pr 2 Fe 14 B in ESR-MRFM experiments. Even so, it appeared that electron spin T 1 and T 1 were still being shortened due to proximity of sample spins to the magnetic ͑metallic͒ tip.…”
Section: G From Sample-on-cantilever To Magnet-on-cantilever Experimmentioning
confidence: 99%
“…This opened the door to quantitative cantilever magnetometry. 40,[134][135][136] As ever smaller diameter tips were used in MRFM experiments, concern was voiced that thermally induced tip magnetization fluctuations might deleteriously affect sample spins. 137 Magnetization fluctuations would lead to magnetic field fluctuations at the sample spins; the spectral density of these fluctuations at the Larmor frequency could lower T 1 , while the spectral density at the Rabi frequency could lower T 1 .…”
Section: G From Sample-on-cantilever To Magnet-on-cantilever Experimmentioning
confidence: 99%
“…[6][7][8] Magnetization fluctuations in individual sub-micron ferromagnets have been detected through voltage and current noise measurements, 9 SQUID magnetometry, 10 magnetic force microscopy, 11 and, at record sensitivity, by frequency-shift torque magnetometry. [12][13][14][15] The highest-sensitivity cantilever magnetometry studies to date have employed high-compliance cantilevers 16,17 to examine in-plane switching of individual magnetic nanorods. 13,15 Here we present a cantilever magnetometry study of in-plane to out-of-plane magnetization switching and fluctuations in a nickel nanorod at low temperature.…”
Section: Introductionmentioning
confidence: 99%